Combatting Terrorism in ASEAN - Dewi Heniarti, Dini; Wahjoe, Oentoeng; Puspawati, Anita (KnE Social Sciences, 2023)
This study aims to determine the strategic policy in facing the shifting scale of the threat of criminal acts of terrorism as an effort to build security in the Asean Region, because terrorism has become a non-traditional security issue adding to the complexity of geopolitical security discourse and the balance of power. The initial finding in this study is the emergence of a shift in the scale of the threat of terrorism in Southeast Asia as a second front after the Middle East so that collective security sees the state standing for a common goal following the same rules and creating peace. The challenges of regionalism to the development of terrorism must be overcome effectively because it is related to maintaining regional stability and the aspiration to make ASEAN a region free from the threat of terrorism. This study used normative legal research, the target of research materials is secondary data, especially legal materials that are secondary and tertiary (in the form of legal information materials), which are then analyzed qualitatively in the sense of formulating justification through the quality of the legal norm itself, expert opinions/doctrine, and supporting legal information. Keywords: scale of terrorism, Asean, security